2017
DOI: 10.3168/jds.2016-11646
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of semen diluents on the in vitro and in vivo fertility of liquid bull semen

Abstract: Semen 3Murphy et al. 4This study examined the effect of a wide range of semen diluents on both the in vitro and in 5 vivo fertility of liquid bull semen stored for up to 3 days post collection. The semen diluents 6 BioXcell, INRA96 and Caprogen maintained sperm motility best when stored at a constant 7 temperature, however, when used in the field, at an unregulated temperature, BioXcell 8 performed poorly. This study clearly illustrates the importance of in vivo fertility data in 9 assessing semen diluents. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 41 publications
4
23
1
4
Order By: Relevance
“…Moreover, this predominantly field study revealed that the calving rate was highest when EY extender was used for semen preservation. This supports doubts concerning SL and EY extenders effectiveness (Gil et al, 2000;van Wagtendonk-de Leeuw et al, 2000;Thun et al, 2002;Aires et al, 2003;Crespilho et al, 2012;Murphy et al, 2017). The fact that artificial liposomebased extender did not exhibit such protection during semen chilling showed that other methods to improve the cryoprotective properties of bull semen extenders could be found.…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…Moreover, this predominantly field study revealed that the calving rate was highest when EY extender was used for semen preservation. This supports doubts concerning SL and EY extenders effectiveness (Gil et al, 2000;van Wagtendonk-de Leeuw et al, 2000;Thun et al, 2002;Aires et al, 2003;Crespilho et al, 2012;Murphy et al, 2017). The fact that artificial liposomebased extender did not exhibit such protection during semen chilling showed that other methods to improve the cryoprotective properties of bull semen extenders could be found.…”
Section: Discussionmentioning
confidence: 68%
“…Our results differ according to the extender used, which could indicate their distinct composition. Moreover, our previous study and study of Murphy et al (2017) revealed the distinct effectiveness of LDL across different soybean extenders and protection by themselves alone, respectively. Unfortunately, information about either the precise content of soybean lecithin or other components in extenders is unavailable in commercial extenders.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations